2018
DOI: 10.3390/batteries4010010
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidinium FSI and TFSI-Based Polymerized Ionic Liquids as Electrolytes for High-Temperature Lithium-Ion Batteries

Abstract: Promising electrochemical and dynamical properties, as well as high thermal stability, have been the driving forces behind application of ionic liquids (ILs) and polymerized ionic liquids (PILs) as electrolytes for high-temperature lithium-ion batteries (HT-LIBs). Here, several ternary lithium-salt/IL/PIL electrolytes (PIL el ) have been investigated for synergies of having both FSI and TFSI anions present, primarily in terms of physico-chemical properties, for unique application in HT-LIBs operating at 80 • C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…Pyrrolidinum-based RTILs have also been widely applied in SCs and Li-ion batteries as a solid-state electrolyte [50]. Substitution of the pyrrolidine cation improves the ionic conductivity of ILs-based electrolytes.…”
Section: Pyrrolidinum-based Ilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrrolidinum-based RTILs have also been widely applied in SCs and Li-ion batteries as a solid-state electrolyte [50]. Substitution of the pyrrolidine cation improves the ionic conductivity of ILs-based electrolytes.…”
Section: Pyrrolidinum-based Ilsmentioning
confidence: 99%
“…Lazzari, M. et al reported that the capacitance of AC electrodes and Pyr 14 TFSI/(EMIM)(TFSI) electrolyte-based SCs were greatly influenced by the polarization of the cation parts of the ionic liquids on the surface of AC electrodes [55,56]. However, a lot of research work is going on all over the world on pyrrolidinum-based ILs for Li-ion and SC applications, but low-temperature conductivity and poor cycle life hinder its market application due to larger non-polar or surfactant ILs [50,57]. Quezada, D. et al designed a safer Li-ion battery using zinc stannate as the anodic material and 1 M-LiNTF 2 solution in 1-methyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide ((MPPyr)(TFSI)) or 1-butyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide ((BMPyr)(TFSI)) as ILs electrolytes.…”
Section: Pyrrolidinum-based Ilsmentioning
confidence: 99%
“…Despite the higher electrochemical performances in liquid form, the use of C 4 mpyrFSI electrolytes with polymer matrices is not commonly studied. Kerner et al [190] synthesized PIL-based electrolytes, where one set contained C 4 mpyrTFSI, and another set contained C 4 mpyrFSI. Both electrolytes tested with LFP yielded electrode discharge capacities above 140 mAh g −1 at 80 • C when 0.5 C rate was utilized.…”
Section: Mpyrfsi-based Polymersmentioning
confidence: 99%
“…The PDADMA TFSA showing highest conductivity was further utilized for the synthesis of ion gels containing N -butyl- N -methylpyrrolidinium TFSA (Pyr 14 TFSA) and LiTFSA in various compositions . Recently, PDADMA based gels with high lithium concentrations were investigated, as well as gels containing two different anions, FSA and TFSA …”
Section: Introductionmentioning
confidence: 99%